HIV-related thought avoidance, sexual risk, and alcohol use among men who have sex with men. Issue 7 (3rd July 2018) - Pérez, Ashley E.; Wray, Tyler B.; Celio, Mark A.; Monti, Peter M.
ABSTRACT: HIV-related "cognitive escape" refers to a tendency to avoid thoughts associated with HIV, which may be particularly common among men who have sex with men (MSM) who are often inundated with HIV information, potentially to the point of fatigue. HIV-related cognitive escape is associated with increased sexual risk behaviors, such as condomless sex, and heavier alcohol use patterns. Other studies show that some MSM may use alcohol specifically to facilitate sex. These sexual motives for drinking (SMDs) could be one mechanism whereby cognitive escape leads to health risk behaviors. In this study, we tested models exploring whether cognitive escape was associated with markers of sex risk (condom use, number of sex partners) and alcohol use/problems, and examined whether SMDs mediated these associations. Heavy drinking, HIV-negative men ( N  = 196) aged ≥ 21 years who self-reported past year condomless anal sex with men completed assessments as part of a larger study. Results suggest that cognitive escape was associated with higher number of anal sex partners (incidence rate ratio [ IRR ] = 1.50, SE  = 0.04, p  < .001), decreased condom use ( B  = −0.30, SE  = 0.14, p  = .028), and increased alcohol-related problems ( IRR  = 1.28, SE  = 0.07, p  = .001) but not with drinking quantity. Sexual motives for drinking appeared to partially mediate the observed relationship between cognitive escape and alcohol-related problems, but other relationships did not show evidence of mediation. Findings suggest that those who tend to avoid HIV-related thoughts may be at increased risk for HIV and alcohol-related problems. Drinking to facilitate sex may partially account for the higher risk for alcohol-related problems conferred by cognitive escape. Alcohol interventions for MSM may be more effective if they address alcohol's role in coping with HIV threat and in facilitating sex under these circumstances.